MINIMALISIR PUPUK NPK 16-16-16 DENGAN APLIKASI POC KULIT NANAS PADA TANAMAN TERUNG UNGU (Solanum melongena L) - Kikie Swandi Lase; Yunida Berliana; Dedi Kurniawan; Nina Unzila Angkat (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2023)
Purple eggplant (Solanum melongena L.) is a vegetable widely grown in Indonesia. This research to determine the effect of applying NPK 16-16-16 combined with pineapple peel POC on the growth and yield eggplant plants. The research was conducted in a community garden in Medan Helvetia District, North Sumatra. The research used two treatment factors with a Factorial Randomized Group Design (RAK). factor1 is the dose of NPK 16-16-16 which consists four levels: N0 (control), N1 (10 grams/plant), N2 (20 grams/plant), and N3 (30 grams/plant). Factor2 POC of pineapple skin consists four levels: P1 (50 ml POC + 950 ml water = 1 L/Plot), P2 (100 ml POC + 900 ml water = 1 L/Plot), P3 (150 ml POC + 850 ml water = 1 L/Plot), and P4 (200 ml POC + 800 ml water = 1 L/Plot). Parameters a plant height (cm), number branches, age harvest (days), fruit weight plant (gr), number of fruit plant, and fruit weight plot. The research results NPK 16-16-16 fertilizer had a impact on plant height, number of branches, age at harvest, fruit weight per plant, number of fruit per plant, and fruit weight per plot. The best dose was 20 g/plant (N2) . Pineapple peel POC application also affected plant height at 5 WAP, number of branches, fruit weight per plant, number of fruit per plant, and fruit weight per plot. The best results are using combination of 20 g/plant NPK 16-16-16 (N2) and 150 ml pineapple skin POC application + 850 ml water.